Pengaruh Fear of Missing Out (FOMO) Terhadap Perilaku Impulse Buying pada Konsumen Generasi Z di TikTok: Studi Literatur - Ai Karlina; Anjani (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
The rapid growth of TikTok as a social commerce platform has shaped new consumption patterns among Generation Z through easy access to information, interactive features, and high exposure to marketing content. One psychological factor believed to reinforce this tendency is Fear of Missing Out (FOMO), an anxious feeling that arises when individuals perceive themselves as at risk of missing out on trends, information, or important opportunities in the digital sphere. This study aims to examine the influence of FOMO on impulsive buying behavior among Generation Z TikTok users using a literature review method. The review synthesizes relevant national and international journals published between 2013 and 2025. The results show that FOMO plays a significant role in driving impulsive buying, particularly when users are exposed to TikTok features such as viral content, time-limited offers, promotional countdowns, limited stock notifications, and live shopping sessions that enable direct interaction with sellers and influencers. Unlike previous studies that generally focus on a single feature or platform, this study proposes a conceptual framework that integrates multiple TikTok features into one model linking FOMO and impulsive buying. This exposure generates emotional pressure that makes decision-making faster and less rational. These findings underline the importance of improving digital literacy so that Generation Z can better manage consumptive urges amid increasingly aggressive marketing strategies. This study concludes that FOMO is the key psychological factor linking TikTok's marketing strategy with the emergence of impulsive buying behavior, and recommends further quantitative research to measure this influence more thoroughly.